Legality of Equivalent Form Concepts For Substance In The Perspective of Divine Balance - Agung Budi Sulistyo (The Indonesian Journal of Accounting Research, 2014)
Abstract: This article uses a qualitative research approach with the interpretation of nash. The purpose of this research would like to reformulate the concept of substance over form to make it more equitable and to describe the reality of the real accounting. As for the method of al-manhaj fi tafsir al, ' ilmi wa sunnah are the base methods for doing scholarly critique over the concept of substance over form and offers a new concept that is more complete and holistic. This resulted in a research study of the rationality of thought will be the need to reconstruct and realignment of the concept of substance over form into form equivalents to substance use so that current accounting practices may run over the values of truth, honesty and can be accounted for. The form equivalent to substance use represent similarities between information that is happening (substance use) with the media for presenting it (form). This equality would bring better definition to the actors and users of accounting information.Abstrak: Artikel ini menggunakan pendekatan penelitian kualitatif dengan interpretasi nash. Tujuan dari penelitian ini adalah untuk merumuskan kembali konsep substansi di atas bentuk untuk membuatnya lebih adil dan untuk menggambarkan realitas akuntansi nyata. Adapun metode al-manhaj fi tafsir al 'ilmi wa sunnah adalah metode dasar untuk melakukan kritik ilmiah atas konsep substansi atas bentuk dan menawarkan konsep baru yang lebih lengkap dan holistik. Hal ini menghasilkan studi penelitian tentang rasionalitas pemikiran akan kebutuhan untuk merekonstruksi dan penataan kembali konsep substansi di atas bentuk ke bentuk setara dengan penggunaan zat agar praktik akuntansi saat ini dapat berjalan di atas nilai-nilai kebenaran, kejujuran dan dapat dicatat. Bentuk yang setara dengan penggunaan zat mewakili kesamaan antara informasi yang terjadi (penggunaan zat) dengan media untuk menyajikannya (bentuk). Kesetaraan ini akan membawa definisi yang lebih baik untuk para pelaku dan pengguna informasi akuntansi.